THE EFFECTIVENESS OF PROMOTION PROGRAM TOWARDS PROSPECTIVE STUDENTS AT POLYTECHNIC APP USING THE EPIC MODEL - Faisal H. Batubara (International Journal Management and Economic, 2022)
The purpose of the study is to Know the Effectiveness of Promotion Program Against Prospective Students at Polytechnic APP. Methods of data collection by interview and questioner survey, data analysis conducted by using EPIC Model method. EPIC Model is used to analyze the impact of communication in promotion. This method was discovered by AC research and research institute. Nielsen, and consists of four complementary dimensions of empathy, persuasion, impact and communication. The population used is prospective students who register and who has become a new student POLITEKNIK APP Jakarta. The sampling technique used by the writer is Simple Random Sampling by giving opportunity to all representing school population who have got promotion from APP Polytechnic, through event of stand edufair, presentation, internet (APP website) and print promo media. The results of the research are as follows: The effectiveness of APP-Jakarta Polytechnics promotion program calculated in the EPIC Model consisting of Empathic Dimension (3.89 = Effective), Persuasion Dimension (4.05 = Effective), Dimensional Impact (3.76 = Effective) and Communication Dimensions (3.94 = Effective) resulted in that the promotion program undertaken by APP-Jakarta Polytechnic has been effectively stated in EPIC RATE that is 3.91 because it is in the effective scale range. Various kinds of promotions APP-Jakarta Polytechnic run, online promotion is the most effective than offline promotion because according to promotion team, target market APP-Jakarta Polytechnic know about APP-Jakarta Polytechnic through searching in google and fill out catalog request at web Polytechnic APP-Jakarta to get more information. So it can be concluded that how the internet is very easy for someone in obtaining information abaut APP-Jakarta Polytechnicto be more fast and efficient.